Quantification of Volatile Acetone Oligomers Using Ion-Mobility Spectrometry - Tobias Hüppe; Dominik Lorenz; Felix Maurer; Tobias Fink; Ramona Klumpp; Sascha Kreuer (Journal of Analytical Methods in Chemistry)
Background. Volatile acetone is a potential biomarker that is elevated in various disease states. Measuring acetone in exhaled breath is complicated by the fact that the molecule might be present as both monomers and dimers, but in inconsistent ratios. Ignoring the molecular form leads to incorrect measured concentrations. Our first goal was to evaluate the monomer-dimer ratio in ambient air, critically ill patients, and rats. Our second goal was to confirm the accuracy of the combined (monomer and dimer) analysis by comparison to a reference calibration system. Methods. Volatile acetone intensities from exhaled air of ten intubated, critically ill patients, and ten ventilated Sprague-Dawley rats were recorded using ion-mobility spectrometry. Acetone concentrations in ambient air in an intensive care unit and in a laboratory were determined over 24 hours. The calibration reference was pure acetone vaporized by a gas generator at concentrations from 5 to 45 ppbv (parts per billion by volume). Results. Acetone concentrations in ambient laboratory air were only slightly greater (5.6 ppbv; 95% CI 5.1–6.2) than in ambient air in an intensive care unit (5.1 ppbv; 95% CI 4.4–5.5; p<0.001). Exhaled acetone concentrations were only slightly greater in rats (10.3 ppbv; 95% CI 9.7–10.9) than in critically ill patients (9.5 ppbv; 95% CI 7.9–11.1; p<0.001). Vaporization yielded acetone monomers (1.3–5.3 mV) and dimers (1.4–621 mV). Acetone concentrations (ppbv) and corresponding acetone monomer and dimer intensities (mV) revealed a high coefficient of determination (R2 = 0.96). The calibration curve for acetone concentration (ppbv) and total acetone (monomers added to twice the dimers; mV) was described by the exponential growth 3-parameter model, with an R2 = 0.98. Conclusion. The ratio of acetone monomer and dimer is inconsistent and varies in ambient air from place-to-place and across individual humans and rats. Monomers and dimers must therefore be considered when quantifying acetone. Combining the two accurately assesses total volatile acetone.